Pharmaceutical Industry discursives and the marketization of nursing work: a case example - Springer, Rusla Anne (Nursing philosophy, 2011)
Increasing pharmaceutical industry presence in health care research and practice has evoked critical social, political, economic, and ethical questions and concern among health care providers, ethicists, economists, and the general citizenry. The case example presented of the ‘marketization’ of nursing practice not only reveals the magnitude of the purview of the pharmaceutical industry, it demonstrates how that industry imparts effect upon the organization of nursing work, an area of health care professional practice where the ethical polemic of pharmaceutical industry involvement and influence has been largely ignored, and the profession of nursing conspicuously silent. Drawing on a Foucauldian dispositive analysis that troubled the complex apparatus responsible for the production of knowledge and action in the neurology subspecialty of multiple sclerosis (MS), the case discloses how the pharmaceutical industry has created compliance and adherence as clinical imperatives in the practice of MS nursing. The case makes explicit the conscious transformative self-action undertaken by MS nurses as a result of their subjectivation (marketization) and demonstrates how MS nurses have become pawns in pharmaceutical industry strategic games of power, truth, identity, and wealth creation by turning their clinical practice settings into heterodiscursive spaces of surveillance and persuasion. MS nurses have become instruments of the pharmaceutical industry, and their clinical practices ordered, organized, limited, constrained, and marketized as a result.